Presence of Trypanosoma vivax DNA in cattle semen and reproductive tissues and related changes in sperm parameters - Couto, Luiz Fellipe Monteiro; Heller, Luciana Maffini; Zapa, Dina María Beltrán; de Moura, Maria Ivete; Costa, Gustavo Lage; de Assis Cavalcante, Alliny Souza; Ribeiro, Nathalia Braz; Bastos, Thiago Souza Azeredo; Ferreira, Lorena Lopes; Soares, Vando Edésio; Lino de Souza, Guilherme Rocha; Cadioli, Fabiano Antônio [UNESP]; et al. (Elsevier, 2022)
The present work investigated the presence of Trypanosoma vivax in semen and reproductive tissues of experimentally infected cattle and evaluated changes in seminal parameters. Two groups of cattle were established: T01 - experimentally infected with T. vivax (n = 8) and T02 - not experimentally infected with T. vivax (n = 8). After infection, blood (every seven days until 182 days post-infection - DPI), semen (7, 14, 35, 56, 70, 120 and 182 DPI) and reproductive tissue (after euthanasia, 182 DPI) were collected to search for T. vivax using different techniques, including PCR, Woo and Brener. Seminal parameters, including turbulence, motility, concentration, and vigor, were also analyzed. Packed cell volume (PCV) of the animals was determined weekly and weight gain was calculated. The PCR revealed T. vivax DNA in 7/56 semen samples of post-infection T01 cattle. Trypanosoma vivax DNA was detected in the semen of 5/8 animals at 7, 14, 56, 70 and 120 DPI, in the testis of four, and in the epididymis and fat located around the testis of two others. Trypomastigote forms of T. vivax were not found in any semen sample. Sperm of T01 cattle had lower turbulence (p ≤ 0.05) at 7, 14, 35, 56, 120 and 182 DPI, lower vigor (p ≤ 0.05) at 120 DPI and more sperm abnormalities (p ≤ 0.05) than T02. Digital dermatitis was observed among T01 cattle. Animals of T01 had lower PCV values than did those of T02 for most of the evaluations performed and T02 animals gained more weight during the experiment. The results highlight the presence of T. vivax DNA in semen of infected cattle and the importance of this disease for male breeding cattle. Further research is needed to determine whether T. vivax can be sexually transmitted in cattle.
Keywords: Ejaculate; Sexual transmission; Sperm motility; Trypanosomosis; Weight gain